IgA nephropathy with mimicking Fabry disease: A case report and literature review. Issue 42 (21st October 2022) - Sun, Liping; Zi, Xinyi; Wang, Zhen; Zhang, Xinzhou
Abstract : Background: Fabry disease (FD) is a rare, inherited disease lysosomal storage disorder caused by the lack of an alpha-galactosidase enzyme. This genetic disease can affect both men and women. The understanding of FD is very important as this condition can be effectively treated. For women who may exhibit normal residual enzyme activity, the diagnosis is more challenging. Case presentation: Herein, we reported on a case of IgA nephropathy and renal disease that mimicked FD in a female patient. The presence of zebra bodies in the cytoplasm of glomerular podocytes is widely accepted as a hallmark pathological manifestation of FD. In the present case, renal biopsy analysis revealed the presence of zebra bodies; however, genetic testing indicated that the patient did not have FD. The mechanisms and causes of zebra body formation remained unclear in the present case. However, the patient responded well to treatment with an angiotensin receptor blocker. Conclusions: The reported findings can be useful for the differential diagnosis of FD and renal diseases in the future. Our results also highlight the clinical significance of zebra bodies in renal disease.